ON COAST LINE OSCILLATIONS DURING LAST DECADES. BORSHI BEACH CASE, ALBANIAN RIVIERA - Marku, S.; Doda, V. (Bulletin of the Geological Society of Greece, 2016)
The oscillations of coast line in Albania, and simultaneously the Quaternary deposits in Albania were little studied until the decade of 90th of 20th century. Up to now, the studies consider those deposits as fluvial sediment; meanwhile, the coast line was categorized as of erosional and accumulative type. In those studies, the role of sea waves and euastatic change of sea level in the process of sediment supply in coastline is neglected. Transgression and regression was interpreted according to Theory of Geosynclinals, as tectonic subsidence or uplift of continental area. From observations in Borshi beach, during August 2013 and September 2015, result that the sediment in this area originate mainly from the erosion of coast line rocks, and less from sediments transported by continental flows. Some traces of marine sediments inside the continental area, in a higher hypsometric quote regarding the actual coastline traces of erosion in some infrastructure works dated of the decade 70’ and 80’ of 20th century, are argument of a temporal rise of sea level during the decade 90’ of past century.